Persona e identità personale (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper analyzes the relations between the personalist principle and the right to personal identity. This right reflects the recognition of the centrality of the human person into the Italian legal system. After examining the main contents of the right to personal identity, the Author focuses on the right of self-determination in end-of-life issues. Such last aspect is analyzed through the perspective of judgement n. 242 of 2019 of the Constitutional Court, about the «Cappato case».
Keywords: Personal identity; personalist principle; end-of-life; biological truth; sexual identity